2013
DOI: 10.1016/j.devcel.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Exo70 Generates Membrane Curvature for Morphogenesis and Cell Migration

Abstract: Dynamic shape changes of the plasma membrane are fundamental to many processes ranging from morphogenesis and cell migration to phagocytosis and viral propagation. Here we demonstrate that Exo70, a component of the exocyst complex, induces tubular membrane invaginations towards the lumen of synthetic vesicles in vitro and generates protrusions on the surface of cells. Biochemical analyses using Exo70 mutants and independent molecular dynamics simulations based on Exo70 structure demonstrate that Exo70 generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
123
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 57 publications
7
123
0
Order By: Relevance
“…This complex was originally proposed to function in post-Golgi secretion/exocytosis by tethering exocytic vesicles with the PM (12)(13)(14). Consistent with this idea, the exocyst localizes to the PM where exocytosis actively occurs and has been implicated in many cellular trafficking processes including polarized budding in yeast (14), neurite growth in neurons (15), GLUT4 membrane insertion in fat cells (16), and cell migration (17)(18)(19). Recent studies have revealed an association between the exocyst and recycling endosome-localized proteins, such as Arf6 (20), AP1B (21), and Rab11 (22), and the presence of exocyst on multiple populations of endosomes (23).…”
mentioning
confidence: 81%
“…This complex was originally proposed to function in post-Golgi secretion/exocytosis by tethering exocytic vesicles with the PM (12)(13)(14). Consistent with this idea, the exocyst localizes to the PM where exocytosis actively occurs and has been implicated in many cellular trafficking processes including polarized budding in yeast (14), neurite growth in neurons (15), GLUT4 membrane insertion in fat cells (16), and cell migration (17)(18)(19). Recent studies have revealed an association between the exocyst and recycling endosome-localized proteins, such as Arf6 (20), AP1B (21), and Rab11 (22), and the presence of exocyst on multiple populations of endosomes (23).…”
mentioning
confidence: 81%
“…In addition to the holo-complex, free pools of certain subunits and sub-complexes have also been identified by biochemical fractionation experiments (Guo et al, 1999a;Jin et al, 2005;Moskalenko et al, 2003;Morgera et al, 2012;Zhao et al, 2013). The physiological significance of the different sub-complexes still needs to be investigated.…”
Section: Molecular Organization Of the Exocyst Complexmentioning
confidence: 99%
“…Furthermore, Sec3 and some of the Exo70 proteins are localized to the bud tip even in the absence of actin cables, which mediate the polarized delivery of secretory vesicles (Finger et al, 1998;Boyd et al, 2004;Zhang et al, 2008). In fission yeast and mammals, however, Sec3 and Exo70 were found to associate with vesicles as well as the plasma membrane (Yeaman et al, 2004;Liu et al, 2007;Andersen and Yeaman, 2010;Bendezu et al, 2012;Zhao et al, 2013). It is possible that, in these cells, all of the exocyst subunits can be transported on vesicles; once they arrive at the destination, Sec3 and Exo70 might then 'anchor' the exocyst and vesicles to the plasma membrane through their physical association with PI(4,5)P 2 .…”
Section: The Exocyst In Vesicle Tetheringmentioning
confidence: 99%
See 1 more Smart Citation
“…T he EXO70 (exocyst component of 70 kDa) protein is a component of the evolutionarily conserved octameric exocyst complex that tethers post-Golgi vesicles to the plasma membrane before SNARE-mediated membrane fusion (1). As an important component of the exocyst complex that mediates exocytosis, EXO70 regulates, for example, neurite outgrowth, epithelial cell polarity establishment, cell motility, and cell morphogenesis in animal cells (2)(3)(4)(5)(6). In plants, EXO70 proteins participate in polarized pollen tube growth, root hair growth, deposition of cell wall material, cell plate initiation and maturation, defense, and autophagy (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%